To Improve Health and Health care (Jossey-Bass, 2004)
To further its mission of improving the health and health care of all Americans, the RWJF strives to foster innovation, develop ideas, disseminate information, and enable committed people to devote their energies to improving the nation's well-being. As part of the Foundation's efforts to inform the public, To Improve Health and Health Care, the on-going anthology of The Robert Wood Johnson Foundation, provides an in-depth look into the programs it funds. Written for policy makers and practitioners, the series offers valuable lessons for developing plans for the coming years.